Evolution of Fiscal Decentralisation in OECD Countries: A Club Convergence Analysis - Francisco J. Delgado; Maria J. Presno (Amfiteatru Economic, 2023)
We study the fiscal decentralisation patterns in OECD countries through a club convergence approach. Our analysis covers 30 countries spanning 1995 to 2018 and considers the noncentral expenditure and revenue sides with two perspectives, as percentage of GDP and as percentage of the total government expenditure and revenue. The results show differences between the expenditure and revenue sides, but with five and six clubs on both sides for the GDP and total government perspectives, respectively. These results allow one to establish a typology based on the four dimensions analysed. In addition, our results suggest a divergent impact of the Great Recession at the overall level of countries and under the expenditure and revenue perspectives; however, simultaneously, that economic downturn seems to have reinforced the process of convergence within clubs under the expenditure perspective. We also study the dynamics of convergence over time using a rolling window estimation, for all countries and the clubs.
Keywords: H77; H10; C01; 330; Decentralisation; club convergence; OECD; Great Recession.